Association of Peripheral Arterial Disease (PAD) in Type 2 Diabetics with Various risk factors - Madeeha Nazar, Hamza Abid, Fazal-Ur-Rehman, Nafia Tahir, Rana Shakil Ahmad (Journal of Rawalpindi Medical College, 2018)
Background:To find out the prevalence of Peripheral Arterial Disease (PAD) in Type 2 diabetic population and to evaluate its association with age, gender, hypertension, smoking and treatment of diabetes. Methods: In this cross sectional study 78 diabetic patients were enrolled. Inclusion criteria was both gender and more than 30 years of age. Patients with type 1 Diabetes Mellitus (blood fasting >126 mg/dl) , hyperlipidemias (triglyceride >150mg/dl or LDL >100mg/dl), deranged creatinine (>1.1) or BMI of more than 30 were excluded from this study. BMI was .For ankle brachial index (ABI) the measurements were done in supine position with a hand held doppler.Systolic pressure were measured at both dorsalis pedis and posterior tibial artery. The higher of the two were used to calculate ABI. Systolic pressures were measured at brachial level as well. ABI was calculated by dividing ankle systolic pressure by brachial systolic pressure of the same side. Results: Out of total 73 cases, peripheral arterial disease was found 77.6% patients. Association of various factors like hypertension, gender, age, diabetes treatment and smoking status with peripheral arterial disease was explored and no statistically significant association was observed with p values less than 0.05. Conclusion: The concurrent occurrence of peripheral arterial disease was found to be markedly high in type 2 diabetic patients.